PENGARUH AUDIT CLIENT TENURE, AUDIT LAG, OPINION SHOPPING, RASIO LIKUIDITAS, DAN RASIO LEVERAGE TERHADAP OPINI AUDIT GOING CONCERN - Saraswati, Agustina Ayu; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2022)
This study aims to empirically the influence factors on the probably of receiving going concern opinion on the manufacturing companies listed on Indonesia Stock Exchange in 2015-2019. The independent variables used in this study are audit client tenure, audit lag, opinion shopping, liquidity ratio and leverage ratio. While the dependent variable is going concern audit opinion.This study uses secondary data from financial statements of manufacturing companies listed on Indonesia Stock Exchange in 2015 - 2019. The sampling method used is purposive sampling. The sample consists of 90 samples of financial reports that listed on Indonesia Stock Exchange period 2015-2019. The analysis method that was used in this study was regression test. The result of this study shows that the independent variables are audit client tenure, audit lag, opinion shopping and leverage ratio has significant influence towards going concern audit opinion. Meanwhile, liquidity ratio do not influence going concern audit opinion.